2009
DOI: 10.1007/s10457-008-9198-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shade and bird exclusion on arthropods and leaf damage on coffee farms in Jamaica’s Blue Mountains

Abstract: Abstracts The effects of overstory trees and birds on coffee pests are poorly understood. This study documents (a) the effect of bird exclusion on foliagedwelling arthropod abundance and insect-caused leaf damage, and (b) the relationships between vegetation complexity and insect abundance, leaf damage, and prevalence of fungal leaf symptoms on coffee farms in the Blue Mountains of Jamaica, West Indies. Overall arthropod abundance was reduced inside bird-proof exclosures, and this corresponded to reduced insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 41 publications
0
33
1
Order By: Relevance
“…Although coffee farmers used 24 fruit tree species as part of the entire shade complement, the fruits of which were harvested for personal use or sold to supplement incomes, their contribution to fruit incomes varied according to high or low elevation. A possible reason for this difference may be due to the use of fewer fruit trees by coffee farmers to provide shade for coffee plants at higher elevations, because it is believed that the ever-present mist cover provides ''shade'' enough for coffee shrubs, and planting more trees will increase leaf spot symptoms and reduce yields (Robinson 2006;Kellermann et al 2008;Johnson et al 2009;Willis 2015). Musaceous species played an important role in the southeastern Blue Mountain coffee systems, with bananas having an even spread at high and low elevations.…”
Section: Discussionmentioning
confidence: 99%
“…Although coffee farmers used 24 fruit tree species as part of the entire shade complement, the fruits of which were harvested for personal use or sold to supplement incomes, their contribution to fruit incomes varied according to high or low elevation. A possible reason for this difference may be due to the use of fewer fruit trees by coffee farmers to provide shade for coffee plants at higher elevations, because it is believed that the ever-present mist cover provides ''shade'' enough for coffee shrubs, and planting more trees will increase leaf spot symptoms and reduce yields (Robinson 2006;Kellermann et al 2008;Johnson et al 2009;Willis 2015). Musaceous species played an important role in the southeastern Blue Mountain coffee systems, with bananas having an even spread at high and low elevations.…”
Section: Discussionmentioning
confidence: 99%
“…Skorupa and Hothem, 1985) and the field continued to be pursued in some developing countries, especially India (Ali, 1980). Even though economic ornithology has almost disappeared as a separate field of study, the interest in this topic persists (for a review of studies on the role of birds in pest control, see Kirk et al, 1996), and recently has been revived through the lens of ecosystem services (Jedlicka et al, 2011;Johnson et al, 2009;Kellermann et al, 2008;Koh, 2008;Sekercioglu, 2006;Whelan et al, 2010Whelan et al, , 2008. With new ecological knowledge, modern research has been able to overcome many of the limitations that hindered the development of economic ornithology at the turn of the 20th century.…”
Section: Discussion -Lessons For Ecosystem Servicesmentioning
confidence: 99%
“…Greenberg and colleagues (2000) excluded birds (and bats) from individual coffee trees and demonstrated a shift in abundance of large arthropods in the treatment. Exclosure experiments in Jamaica ( Johnson et al 2009( Johnson et al , 2010 and Costa Rica (Karp & Daily 2013, Karp et al 2013) demonstrated that birds (and/or bats) significantly reduced the incidence of the main coffee pest, the coffee berry borer, which translates into an economic value of up to US$310 per hectare. Reviewing the literature on exclosure experiments in coffee and cacao, Van Bael and colleagues (2008) conclude that top-down effects of birds (and bats) on arthropods are common and strong, including effects on both herbivorous and carnivorous arthropods.…”
Section: Vertebrate and Invertebrate Carnivoresmentioning
confidence: 99%